Corrigendum: Jeremiah 29:5-7 reread through the lens of posttraumatic growth - X. Li (Acta Theologica)
Jeremiah 29:5-7 is well known for exhorting the exiles to settle down and pray for the welfare of Babylon. The idea of settling down conflicts with the prophecy of returning home in the book of Jeremiah, and it sounds odd to encourage prayer for the enemy. Typical solutions focus on the strategy of survival. However, these solutions are not convincing enough because the language used in Jeremiah 29:5-7 indicates that the exhortation involves not survival but restoration. Given the background of national trauma behind the book of Jeremiah, this article proposes rereading Jeremiah 29:5-7 from the perspective of posttraumatic growth (PTG). Accordingly, the exhortation to settle down reflects the domain of appreciation of life in PTG, and the exhortation to pray for Babylon indicates the belief in a just world for self (BJW-self), which is closely related to PTG and entails forgiving others.